Effects of weather characteristics on blooming dates in an apple gene bank plantation between 1984 and 2001 - Lakatos, L.; Szabó, T.; Racskó, J.; Soltész, M.; Szabó, Z.; Nagy, J.; Nyéki, J. (International Journal of Horticultural Science, 2006)
The aims of this paper was to investigate the flowering characteristic of apples and their relationship to meteorological parameters. The trees observed are grown at Ujfehert6, Eastern Hungary in the plantation of an assortment (gene bank) with 586 apple varieties. Each of the varieties were observed as for their dates of subsequent phenophases, the beginning of bloom, main bloom and the end of bloom over a period between 1984 and 2001. During this period the meteorological data-base keeps the following variables: daily means of temperature (°C), daily maximum temperature (°C), daily minimum temperature (°C), daily precipitation sums (mm), daily sums of sunny hours, daily means of the differences between the day-time and night-time temperatures (°C), average differences between temperatures of successive daily means (°C). Between the 90th and 147th day of the year over the 18 years of observation. The early blooming varieties start blooming at 10-21 April. The varieties of intermediate bloom start at the interval 20 April to 3 May, whereas the late blooming group start at 2-10 May. Among the meteorological variables of the former autumnal and hibernal periods, the hibernal maxima were the most active factor influencing the start of bloom in the subsequent spring.